Study on risk prediction and intervention coping of mild cognitive impairment in patients with hypertension. (March 2023) - Bao, Wuren; Qu, Ying; Gong, Guomei; Zhang, Jifeng
Abstract : Background: While the ageing population is increasing, diseases such as senile dementia and hypertension have gradually become important health risks for the elderly. The existing research shows that long-term hypertension will affect the structure and function of cerebral vessels, leading to the decline of cerebrovascular compliance, vascular deformation, cerebral blood flow reduction and other problems. The occurrence of these conditions will lead to the decline of the brain's self-regulation ability, which will lead to cognitive decline and dementia. The study will analyze the risk factors of mild cognitive impairment (MCI) in hypertensive patients, and determine the regulatory role between adaptation and cognitive function in the treatment of hypertensive patients. Subjects and Methods: In this study, 180 hypertensive patients were investigated to analyze their cognitive factors and functional status. The investigation was completed by the Montreal Cognitive Assessment (MoCA). After the investigation, SPSS 25.0 software was used to analyze the data and screen the independent risk factors of mild cognitive impairment. The experimental results are shown in Table 1 . Results: As shown in Table 1, 124 of 180 hypertensive patients developed MCI, with a prevalence rate of 68.9%. It can be seen from the table that the total score and scores of each dimension in the MCI group were significantly lower than those in the normal cognitive function group ( P < 0.05), with the largest difference being delayed recall and executive function. Conclusions: In this study, the research center was placed at risk of mild cognitive impairment in hypertensive patients. Through the MoCA scale investigation experiment, it was found that 124 of 180 hypertensive patients had a lower cognitive function in all dimensions than normal. The experiment shows that the problems such as micro hemorrhage caused by hypertension and the increase of cerebrovascular events affect the cognitive function of the elderly, which is obviously reflected in memory and executive ability. Acknowledgements: The research is supported by: The Study of the Effect of Health Education Based on Teach-back and PRECEDE Model on Elderly Hypertensive Patients in the Community, supported by Fundamental Research Funds for Universities of Inner Mongolia Autonomous Region; The Construction of Human Care Training Courses for Nursing Students Based on Health Care of Elderly Patients with Chronic Diseases, supported by Higher Education Teaching Reform Project of National Ethnic Affairs Commission, 2021 (No.21083); An Exploration of the Ideological and Political Construction in Human Care Training Courses of Higher Education for Nursing Students in the New Era, supported by a grant from the Education and Science Project of Inner Mongolia Autonomous Region during the 14th Five-Year Plan Period, 2021 (No.NGJGH2021145).